تصميم المنهج وكتاب تعليم اللغة العربية للمرحلة الجامعية في ضوء معايير الإطار الوطني الإندونيسي للمؤهلات (KKNI) - Fatwiah Noor (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The teaching and learning process during the pandemic has challenges for teachers and students. Both must go through the obstacles in online learning that must be implemented to achieve the learning goals and objectives. One way to achieve learning goals and objectives is by choosing an appropriate strategy. This study aims to examine the implementation of the inquiry method in an online class of excellent students development program implemented by UPB UIN Antasari Banjarmasin, Indonesia and student satisfaction with the learning process. As many as 95.31% of students stated that they were satisfied with the learning process, and 96.17% were delighted with the tutor's performance. This study's results show that the inquiry strategy applies by providing an issue or topic. This is then analyzed by students and discussed with the teacher together. This strategy is the right step to improving students' abilities in learning foreign languages by making the learning process more meaningful. This is done by providing experiences to use in their daily lives.